Fibronectin as predictor of cirrhosis in men who abuse alcohol. Issue 6637 (11th June 1988) - Junge, Jette; Bentsen, Kirsten D; Christoffersen, Per; Orholm, Marianne; Sørensen, Thorkild I A; Horn, Thomas
Abstract : In a study of 142 male alcohol abusers without evidence of cirrhosis the presence of intralobular fibronectin in the liver was investigated in relation to the subsequent development of the disease. All 142 initial biopsy samples showed preserved architecture. During a follow up period of 10-13 years 23 patients (16%) developed cirrhosis. Twelve of 110 patients with normal or slightly increased amounts of parenchymal fibronectin in the initial biopsy specimen developed cirrhosis, whereas eight out of 27 patients with moderately increased amounts and three out of five with significantly increased amounts later developed the disease (p<0·005). Semiquantitative assessment of the amount of parenchymal fibronectin at an early stage of alcoholic liver disease is of definite predictive value for the development of cirrhosis.